Cover Feature: Defect Engineering of van der Waals Solids for Electrocatalytic Hydrogen Evolution (Chem. Asian J. 22/2020). Issue 22 (27th October 2020) - Yang, Leping; Yang, Xiaohan; Yu, Lingxiao; Lv, Ruitao
Abstract : Defect engineering in van der Waals solids plays an important role in triggering the catalytic activity of their inert components for the hydrogen evolution reaction (HER). It could efficiently modulate the chemical components and band‐gap states of van der Waals solids, thus impacting the reactants′ capture, activation and release process. In this Minireview, the state‐of‐the‐art progress of defect engineering in van der Waals solids for HER, involving zero‐dimensional defects (e. g., atomic vacancies and heteroatom doping), one‐dimensional defects (e. g., under‐coordinated edges and domain boundaries), two‐dimensional defects (e. g., vertical heterostructures and interfacial distortions), and other typical defects is summarized. In particular, focus is laid on their advantages in material modification and corresponding catalytic mechanisms. In addition, the challenges and perspectives of these catalytic materials in terms of both experimental synthesis and fundamental understanding of the defect structures are also proposed. More information can be found in the Minireview by Ruitao Lv et al.